2013
DOI: 10.1371/journal.pone.0085053
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Mangosteen Extract on H2O2-Induced Cytotoxicity in SK-N-SH Cells and Scopolamine-Induced Memory Impairment in Mice

Abstract: Mangosteen extracts (ME) contain high levels of polyphenolic compounds and antioxidant activity. Protective effects of ME against β-amyloid peptide (Aβ), induced cytotoxicity have been reported. Here, we further studied the protective effects of ME against oxidative stress induced by hydrogen peroxide (H2O2) and polychlorinated biphenyls (PCBs), and demonstrated the protection against memory impairment in mice. The cytoprotective effects of ME were measured as cell viability and the reduction in ROS activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 36 publications
7
49
1
3
Order By: Relevance
“…In this study, the restoration of the intra-cellular ROS level by pre-treatment with LSE showed the protective effects of various concentrations of LSE against H 2 O 2 -induced ROS generation in HepG2. Our results are in agreement with the previous reports showing that the administration of natural products suppress the increased level of intra-cellular ROS generation (Farshori et al, 2013;Molina et al, 2003;Sattayasai et al, 2013;You et al, 2010). It is known that apoptosis-signaling cascades can be initiated by mitochondria impairment (Taveira et al, 2014).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, the restoration of the intra-cellular ROS level by pre-treatment with LSE showed the protective effects of various concentrations of LSE against H 2 O 2 -induced ROS generation in HepG2. Our results are in agreement with the previous reports showing that the administration of natural products suppress the increased level of intra-cellular ROS generation (Farshori et al, 2013;Molina et al, 2003;Sattayasai et al, 2013;You et al, 2010). It is known that apoptosis-signaling cascades can be initiated by mitochondria impairment (Taveira et al, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…crude extracts from natural products exhibited significant cyto-protection against the H 2 O 2 in PC12 and SK-N-SH cells Sattayasai et al, 2013) and in liver cells against other toxicants (Alia et al, 2006;Goya et al, 2007;Martin et al, 2008;Verma et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In vitro and in vivo studies have proven that Garcinia mangostana is characterized by antioxidative and cytoprotective activities due to the presence of phenolic compounds [Phyu & Tangpong, 2014;Sattayasai et al, 2013]. Several studies found that the polyphenolic compounds found in Aegle marmelos, Commiphora mukul, green tea, cinnamon and ginger have hepatoprotective properties in different animal models [Elgawish et al, 2015;Ismail, 2014;Ramesh et al, 2015;Suriyamoorthy et al, 2014].…”
Section: Discussionmentioning
confidence: 99%